(untitled) (Islamic Sciences Journal, 2023)
In this paper the researcher dealt with some definitions such as (the direction, the approach and the method), then has dealt with the old trends and the factors affecting them. Since the emergence of interpretation to the era of codification, and then dealt with interpretation trends from the categorization era to the twentieth century AD, the researcher mentioned the golden age of Islam and the flourishing of science and knowledge at the beginning The Abbasid era, and then the fall of the Caliphate and the scourge and destruction that befell the Islamic world in its east and west, destroying Islamic civilization and burning precious libraries and blogs in all sciences and knowledge, and the Islamic nation fell into a deep sleep until the end of the nineteenth century AD, the Islamic Renaissance, so schools and universities were opened and the country developed administratively Politically, scientifically and culturally, new trends have been emerged in interpretation according to the new era, some of them are good and some are bad. In this research, three main factors have been presented that have a significant impact on the trends of interpretation, which are (the personal qualities of the interpreter, the conditional sciences of interpretation, and the environment or the reality surrounding the interpreter). Interpretations preserve the correct interpretation of the explanatory heritage of the three generations (the Companions, the Followers and the Followers of the Followers